The Rurality of Intimate Partner Femicide: Examining Risk Factors in Queensland - McLachlan, Freya (Violence against women, 2024)
While violence against women and domestic violence can be seen throughout Australia, emerging evidence suggests that intimate partner femicide (IPF) is more common in rural spaces than urban ones. This study examined 100 IPF cases to determine the rate of femicide and frequency of common risk factors in rural areas of Queensland, Australia. The study also explored how victims accessed services and the characteristics of rural IPF and male offenders. Findings indicated that IPF is more common in rural areas and associated risk factors are similar between urban and rural cases. Rural IPF was more likely to occur during a current relationship and offenders were found to be less likely to conceal their actions. These differences suggest that the physical and social isolation of rural spaces may facilitate higher rates IPF. Implications discuss the need for rural-focused policies and responses.